Clinical effectiveness of care managers in collaborative primary health care for patients with depression: 12- and 24-month follow-up of a pragmatic cluster randomized controlled trial - Sandra af Winklerfelt Hammarberg; Cecilia Björkelund; Shabnam Nejati; Maria Magnil; Dominique Hange; Irene Svenningsson; Eva-Lisa Petersson; Malin André; Camilla Udo; Nashmil Ariai; Lars Wallin; Carl Wikberg; et al. (BMC Primary Care, 2022)
Abstract Background In previous studies, we investigated the effects of a care manager intervention for patients with depression treated in primary health care. At 6 months, care management improved depressive symptoms, remission, return to work, and adherence to anti-depressive medication more than care as usual. The aim of this study was to compare the long-term effectiveness of care management and usual care for primary care patients with depression on depressive symptoms, remission, quality of life, self-efficacy, confidence in care, and quality of care 12 and 24 months after the start of the intervention. Methods Cluster randomized controlled trial that included 23 primary care centers (11 intervention, 12 control) in the regions of Västra Götaland and Dalarna, Sweden. Patients ≥18 years with newly diagnosed mild to moderate depression (n = 376: 192 intervention, 184 control) were included. Patients at intervention centers co-developed a structured depression care plan with a care manager. Via 6 to 8 telephone contacts over 12 weeks, the care manager followed up symptoms and treatment, encouraged behavioral activation, provided education, and communicated with the patient’s general practitioner as needed. Patients at control centers received usual care. Adjusted mixed model repeated measure analysis was conducted on data gathered at 12 and 24 months on depressive symptoms and remission (MADRS-S); quality of life (EQ5D); and self-efficacy, confidence in care, and quality of care (study-specific questionnaire). Results The intervention group had less severe depressive symptoms than the control group at 12 (P = 0.02) but not 24 months (P = 0.83). They reported higher quality of life at 12 (P = 0.01) but not 24 months (P = 0.88). Differences in remission and self-efficacy were not significant, but patients in the intervention group were more confident that they could get information (53% vs 38%; P = 0.02) and professional emotional support (51% vs 40%; P = 0.05) from the primary care center. Conclusions Patients with depression who had a care manager maintained their 6-month improvements in symptoms at the 12- and 24-month follow-ups. Without a care manager, recovery could take up to 24 months. Patients with care managers also had significantly more confidence in primary care and belief in future support than controls. Trial registration ClinicalTrials.gov identifier: NCT02378272. Submitted 2/2/2015. Posted 4/3/2015.